Temperature based DC motor speed control - Gary Royston, George (2010)
The speed of a DC motor can be controlled by varying the supply voltage across the two terminals of DC motor and there are many ways of doing so. This project uses control logic for the brushless DC (BLDC) motor speed control which is based on the ambient temperature readings of an analog temperature sensor. The microcontroller will produce a pulse-width modulation (PWM) signal with variable duty cycle based on the temperature data obtained to regulate the motor speed through a MOSFET as switching component to turn ON and OFF at PWM frequency which act as the motor drive. A microcontroller with analog to digital converter (ADC) interface and PWM peripheral will be used in this project to communicate with an analog temperature sensor and to regulate a brushless DC motor speed